CROI 2018: Advances in Basic Science Understanding of HIV - Stevenson, Mario (Top Antivir Med, 2018)
The conference on Retroviruses and Opportunistic Infections represents the most important venue for the dissemination of research advances in HIV and AIDS. The 25th conference, held in Boston, featured presentations that provided insight into the mechanisms of HIV-1 spread in tissues as well as new information on mechanisms of HIV-1 persistence in individuals on effective antiretroviral treatment. The ability of the conference to convey research findings for a general audience is enhanced, to a large part, by preconference workshops. These workshops feature leading researchers who aim to present cutting edge research to a general audience. These sessions rank highly in terms of education and professional value.